Perlindungan Hukum Terhadap Anak Dalam Tindak Pidana Kejahatan Seksual Online - Moh Fakhri Anshori Adhyaksana; Zakiah Noer; Dara Puspitasari (PT Ilmu Data Indonesia, 2026)
This study examines the effectiveness of Law No. 12/2022 on the Crime of Sexual Violence (UU TPKS) and Government Regulation No. 27/2024 in protecting children from cybersexual crimes. Employing normative legal research with statutory and case approaches, the findings indicate a fundamental normative advancement through the criminalization of electronic non-physical sexual harassment under Article 5. However, the empirical reality reveals a minimalist case resolution rate due to the highly abstract nature of the offense elements, an asymmetric digital forensic burden of proof triggering a 70% case file return rate (p-19), and jurisdictional overlaps with the Electronic Information and Transactions Law (UU ITE) due to the absence of a bridging article. Furthermore, law enforcement is impeded by cognitive deficits among officials, inter-institutional fiscal fragmentation, transnational extraterritorial jurisdiction barriers, and a paradigm clash between restorative and retributive justice mechanisms. To realize the principle of the best interests of the child, this study recommends a comprehensive regulatory restructuring. This includes the unification of real-time digital reporting under KPAI, enhancing officials' digital forensic capabilities, material harmonization with the Juvenile Justice System Law (UU SPPA), institutionalizing a five-year special minimum prison sentence for adult offenders, and introducing the strict liability doctrine for digital platform corporations to curb the linear escalation of child exploitation in cyberspace.